THE ROLE OF INDONESIAN MUSLIM WOMEN SCHOLARS (ULAMA PEREMPUAN) IN ISSUING PROGRESSIVE FATWAS ON GENDER AND FAMILY LAW - Ahmed Al- Fahad; Kaito Tanaka; Haruka Sato (Yayasan Adra Karima Hubbi, 2026)
The emergence of Indonesian Muslim women scholars (ulama perempuan) marks a significant transformation in the contemporary Islamic legal discourse on gender and family law. Historically, fatwas have been predominantly issued by male scholars, often reflecting patriarchal interpretations of Islamic jurisprudence. This study aims to examine how ulama perempuan contribute to the development of progressive fatwas that promote gender justice, human dignity, and women’s rights within the framework of Islamic law. The research employs a qualitative descriptive design using content analysis of fatwas, interviews with members of Kongres Ulama Perempuan Indonesia (KUPI), and field observations of community-based legal education programs. The findings reveal that ulama perempuan reinterpret classical texts through a contextual and maqasid al-shariah approach, emphasizing principles of equality, compassion, and social welfare. Their fatwas address critical issues such as child marriage, domestic violence, reproductive rights, and environmental justice, demonstrating the dynamic interplay between religious authority and social advocacy. The study concludes that the intellectual and moral authority of ulama perempuan strengthens the democratization of Islamic jurisprudence in Indonesia and serves as a model for inclusive, gender-responsive Islamic scholarship globally.